IDENTIFIKASI TINGKAT PENGETAHUAN IBU TENTANG DIET CASEIN FREE DAN GLUTEN FREE PADA ANAK AUTIS - Windy Oktaviana; Yufitriana Amir; Ganis Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Autism was the interference which influence in their daily life. The austims sufferance in Indonesia has increase every  single years. A mother has an important role in the growth of the children. This research has a purpose to know the  identification the level of mother knowledge about casein free and gluten free diet to the autism child with quantitative  research with descriptive research design. The sample of research 58 people respondent which get by the inclusion  criteria from some school on SLB Pekanbaru City with using consecutive sampling technique. The measuring technique  is using multiple choice questions to know the mother knowledge about casein free and gluten free diet. The data  analysis which using descriptive. The result of this research shows that from 58 respondent, there are 28 respondent  (48,3%) have a good knowledge which 30 respondent (51,7%) have a less knowledge. This research is recommended to  the mother to be increase  their knowledge about casein free and gluten free diet with the right way to the children.Keywords: Autism, casein free, gluten free, knowledge, mother